'Look into the Book of Life': Muslim musicians, Sufism and postmodern spirituality in Britain. (September 2016) - Morris, Carl
Spirituality has been theorised as a characteristic of late-modern society, a consequence of individualisation and of a relativized marketplace of religion. Drawing on findings from ethnographic fieldwork conducted with Muslim musicians in the UK, the author claims that spirituality can indeed be considered a postmodern discourse of belief – with trans-religious applicability – but that at the same time it can be articulated from within a clear understanding of group/religious membership. The concepts of 'spiritual capital' and 'expressive communalism' are used to explain the ways through which a postmodern discourse of spirituality is utilised by Muslim musicians from within contemporary networks of Sufism in the West. The author suggests the cosmopolitan and inclusive nature of these types of Sufism in Britain – particularly among third and fourth generation Muslims – represents a frontier of religious change in the UK and a challenge to traditional forms of religious authority, discourse and membership.